Flow-induced instabilities of shells of revolution with non-zero Gaussian curvatures conveying fluid. (17th February 2016) - Chang, Gary Han; Modarres-Sadeghi, Yahya
Abstract: We study flow-induced instabilities of axis-symmetric shells of revolution with an arbitrary meridian and non-zero Gaussian curvatures. We consider a fluid–structure interaction (FSI) model based on an inviscid flow model and a thin shell theory. This FSI model is solved using a method that combines the Galerkin technique with the boundary element method (BEM). The present method is capable of investigating the dynamic behavior of doubly‐curved shells in contact with flow without the need for an analytical solution of the perturbed flow potential. Shells of revolution with different values of non-zero Gaussian curvatures are investigated and their behavior is compared to shells with zero Gaussian curvature. It is found that the added mass natural frequencies of shells of revolution are larger than those of conical shells with the same inlet, outlet and length. Shells of revolution, with both positive and negative Gaussian curvatures, lose their instability by buckling, however, shells with negative Gaussian curvatures buckle at modes similar to those observed in uniform and conical shells, while shells with positive Gaussian curvatures buckle with localized deformations close to the area with higher local flow velocities.